Identifikasi Medan untuk Keterlintasan Rel Kereta Api antara GundihâKarangsono Kabupaten Grobogan - Hardjono, Imam (Forum Geografi, 2011)
This reseach aimed to 1) identify the characteristics terrain for railway track between Gundih-Karangsono, 2) evaluate the capability of terrain and faffecting factors of damages on the track. Field survey and laboratory analysis were used to collect stratified sampling based primary data namely slope, points load index, structure of rock, erosion, mass movement, permeability, soil texture, water degree, potential volume change. Secondary data consists of rainfall, topography map, geology map, soil map and landuse map. Factors that cause train stripe between Gundih-Karangsono often experience damage are: points load index in every terrain unit 3 kg/cmÂ² (very weak), soil texturs are clay and clay loam, soil permeabilities are 0,164-0,579 height of water is from 50-57 % and soil volume changing potential very high, from 6,4-6,5 cm.